Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2002)
This issue of Networks is the last in a year that has seen a tightening of constraints, both political and educational, in response to the increasing violence that has characterized relationships between nations, cultures, religions and economic classes. In education, in almost all the richer countries, there has been a tighter focus on "basic skills" and the memorization of an increasingly large body of "core knowledge", assessed through standardized tests, and a concomitant narrowing of the opportunities for student initiative, choice, and sustained investigation of questions and issues that they find personally significant. Teachers feel harried and hurried, with little or no time to explore topics in depth or to seize and develop the "teachable moment".